Utility of a standardized training program for endoscopic diagnosis of early gastrointestinal neoplasia - Chiu, Philip W.; Sano, Yasushi; Uedo, Noriya; Singh, Rajvinder; Ng, Enders K.W.; Aang, Tiing Leong; Chiu, Han Mo; Ho, Shiaw-Hooi; Banerjee, Rupa; Tanaka, Shinji; Li, Xiao Bo; Yao, Fang; Lau, James Y.W.; Yao, Kenshi (Endoscopy International Open, 2019)
Background and study aims Image enhanced endoscopy (IEE) allows endoscopists to improve recognition and characterization of gastrointestinal neoplasia. The Asian Novel Bio-Imaging and Intervention Group (ANBIG) conducted a standardized training program in endoscopic diagnosis and treatment of early gastrointestinal cancers in Asia. We embarked on a study to investigate the effect of this module on endoscopic diagnosis of early gastrointestinal neoplasia.Methods This prospectively collected database was from workshops conducted on training for endoscopic diagnosis of early gastrointestinal neoplasia. All workshops were conducted in a standardized format, which included a pretest, a learning phase consisting of didactic lectures, case discussion, and live demonstration followed by a post-test to assess knowledge gained. The pretest and post-training tests were standardized questions addressing four domains, including basic knowledge of imaging and diagnosis of esophageal, gastric, and colonic neoplasia.Results From November 2013 to November 2016, 41 ANBIG workshops were conducted in 13 countries. A total of 1863 delegates and 40 faculty participated in these workshops. Of the delegates, 627 completed both tests. There was a significant improvement after training in all domains of the tests. There was a trend in general lack of knowledge across all domains for delegates from “low” healthcare cost countries before training. All delegates demonstrated significant improvement in knowledge of all domains after the workshop irrespective of whether they were from “high” or “low” healthcare cost per capita countries.Conclusion A standardized teaching program on IEE improved the diagnostic ability and quality of endoscopists in recognizing early gastrointestinal neoplasia in Asia.